Kinetic resolution of indolines by asymmetric hydroxylamine formation - Gang Wang (Nature Portfolio, 2021)
Catalytic kinetic resolution of amines is a longstanding challenge in chemical synthesis. Here, the authors report on titanium‐catalysed asymmetric oxygenation with hydrogen peroxide for kinetic resolution of secondary amines through oxygenation to produce enantiopure hydroxylamines involving N–O bond formation.